COMPOUNDS AND USES THEREOF TO TREAT TUMORS IN A SUBJECT - DAHMEN HEIKE; ZIMMERMANN ASTRID; GROMBACHER THOMAS; ORTIZ RUIZ MARIA JESUS (2020)
The present invention relates to compounds that can be used to induce immunogenic cell death (ICD). In some instances, two or more compounds are combined to induce ICD. The invention also relates to the combination of ICD-inducing compounds with an agent stimulating the immune system, such as an immune checkpoint inhibitor, in particular, to treat cancer or inhibit tumor growth. 本发明涉及可以用于诱导免疫原性细胞死亡(ICD)的化合物。在一些情况下，两种或更多种化合物被组合以诱导ICD。本发明还涉及ICD诱导化合物与刺激免疫系统的药剂(如免疫检查点抑制剂)的组合，特别是用于治疗癌症或抑制肿瘤生长。